Preparation method of anatase nano-titanium dioxide based on low-temperature alcohol system hydrolysis
Patent Information
- Application Number
- CN202511759352.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-27
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-11-27
AI Technical Summary
该方法虽然可以得到粒径分布均匀的纳米二氧化钛,但操作繁琐需要高温高压水解反应,且所制备的纳米二氧化钛一般为混合晶型
[0021]本发明的有益效果是:本发明基于低温醇体系水解的锐钛型纳米二氧化钛的制备方法通过控制醇、表面分散剂的加入顺序,及低温水解法与三段焙烧工艺相结合,所制得的锐钛型纳米二氧化钛产品收率达到91.2%以上,粒径大小为30.36~36.27nm,同时所制备得到的纳米二氧化钛中锐钛型晶型占96%以上。
Smart Images

Figure CN121573711B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing anatase nano-titanium dioxide, and more particularly to a method for preparing anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis. Background Technology
[0002] Nano titanium dioxide, also known as nano titanium white, is considered the best-performing white pigment in the world due to its non-toxicity, optimal opacity, whiteness, and gloss. It is widely used in industries such as coatings, plastics, papermaking, printing inks, synthetic fibers, rubber, and cosmetics. Nano titanium dioxide is currently one of the most widely used nanomaterials. Its transparency, ultraviolet absorption, low melting point, strong magnetism, and thermal conductivity make it important in many fields, including cosmetics, plastics, coatings, fine ceramics, and catalysts.
[0003] Due to the wide range of applications of nano-titanium dioxide in photocatalysts, gas sensors, and water treatment, research on nano-titanium dioxide has been very active. Nano-titanium dioxide has three common crystal forms: brookite, anatase, and rutile. Among them, anatase nano-titanium dioxide has a high photogenerated carrier mobility rate and a high density of surface hydroxyl groups, and is widely used in photocatalysis and solar power generation, especially in the photocatalytic degradation of indoor air pollutants. The main methods for preparing anatase nano-titanium dioxide include the gas-phase oxidation of titanium tetrachloride, the liquid-phase hydrolysis method, and the sol-gel method. These methods have the disadvantages of complex processes and high costs, and often result in mixed crystal forms and uneven particle size. For example, Chinese invention patent application CN117865215A discloses a method for preparing battery-grade nano-titanium dioxide. This method uses a strong base-weak acid salt as a pH adjuster dissolved in ice water to completely hydrolyze the titanium salt to obtain titanic acid. Then, potassium hydroxide is used as a pH adjuster to further hydrolyze the titanic acid to obtain a titanium complex. The complex is then sheared and dispersed and subjected to a high-temperature and high-pressure hydrothermal reaction. After the reaction, the product is completely calcined to obtain nano-titanium dioxide. This method is relatively cumbersome and uses a high-temperature and high-pressure reaction, which requires high-quality equipment. Moreover, the reaction mechanism is complex and difficult to industrialize. Chinese invention patent application CN115259214A discloses a method for preparing spheroidized nano-titanium dioxide. The method involves obtaining hydrated titanium dioxide precipitate through alcohol hydrolysis of titanium salt, adding a dispersant, and then reacting the hydrated titanium dioxide precipitate with alkaline hydrothermal solution to obtain a hydrated titanium dioxide slurry. This slurry is then refined through high-temperature, high-pressure hydrothermal treatment to obtain nano-hydrated titanium dioxide slurry. After aging, solid-liquid separation is performed, followed by washing and filtration to obtain a purified slurry. The purified slurry is then atomized with nano-water vapor using jet spraying and spray drying to obtain spheroidized powder. Finally, the spheroidized powder is subjected to high-temperature spray free-fall calcination to obtain spheroidized nano-titanium dioxide powder. While this method can yield nano-titanium dioxide with uniform particle size distribution, it is cumbersome, requiring a high-temperature, high-pressure hydrolysis reaction, and the prepared nano-titanium dioxide is generally of a mixed crystalline form. Therefore, providing a simple, easy-to-operate method for preparing pure crystalline nano-titanium dioxide with excellent dispersibility is a pressing issue. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis, which precisely controls the crystal form and particle size of nano-titanium dioxide under the conditions of low-temperature hydrolysis.
[0005] The technical solution adopted by this invention to solve its technical problem is: a method for preparing anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis, comprising the following steps:
[0006] (1) Mix water and alcohol to obtain solution A;
[0007] (2) Add a surface dispersant to the titanium tetrachloride solution and mix thoroughly to obtain solution B;
[0008] (3) Then, under stirring, add solution B dropwise into solution A. After the addition is complete, stop stirring to obtain solution C.
[0009] (4) Add alkali to solution C to adjust the pH to 7-10, then raise the temperature to 70-90℃ and keep it warm for 3-10 hours;
[0010] (5) After step (4) is completed, age for 12 to 36 hours to obtain nano titanium dioxide slurry;
[0011] (6) The nano-titanium dioxide slurry is washed with water and filtered to obtain a purified slurry;
[0012] (7) The purified slurry is calcined to obtain anatase nano-titanium dioxide; the calcination includes low-temperature calcination, primary calcination and secondary calcination, the low-temperature calcination temperature is 400-550℃ and the time is 1-2h, the primary calcination temperature is 600-700℃ and the time is 1-2h, and the secondary calcination temperature is 750-800℃ and the time is 2-4h.
[0013] Furthermore, the alcohol in step (1) is selected from one of n-propanol, n-octanol, isopropanol, ethanol, and butanol.
[0014] Furthermore, in step (1), the volume ratio of water to alcohol is 1:1 to 10.
[0015] Furthermore, in step (2), the surface dispersant is selected from citric acid, polyethylene glycol, sodium dodecyl sulfate, and polyvinylpyrrolidone.
[0016] Furthermore, in step (2), the concentration of the titanium tetrachloride solution is 1.0–1.2 mol / L. -1 The amount of surface dispersant added is 0.1 to 1 wt.% of titanium tetrachloride.
[0017] Furthermore, in step (3), the time for solution B to be added to solution A is 20 to 40 minutes.
[0018] Furthermore, in step (7), the purified slurry is heated to 400-550°C at a rate of 1-3°C / min, and then calcined at low temperature for 1-2 hours.
[0019] Furthermore, the first roasting in step (7) involves heating the material after low-temperature roasting to 600-700°C at a rate of 4-6°C / min, and then roasting for 1-2 hours.
[0020] Furthermore, the secondary roasting in step (7) involves heating the material after the first roasting to 750-800°C at a rate of 2-4°C / min, and then roasting it for 2-4 hours.
[0021] The beneficial effects of this invention are as follows: The preparation method of anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis of this invention controls the order of addition of alcohol and surface dispersant, and combines low-temperature hydrolysis with a three-stage calcination process. The yield of the anatase nano-titanium dioxide product obtained is over 91.2%, and the particle size is 30.36-36.27 nm. At the same time, the anatase crystal form accounts for more than 96% of the nano-titanium dioxide obtained. Attached Figure Description
[0022] Figure 1 This is the XRD pattern of the nano-titanium dioxide powder obtained in Example 1 of the present invention;
[0023] Figure 2 This is the XRD pattern of the nano-titanium dioxide powder obtained in Example 2 of the present invention;
[0024] Figure 3 This is the XRD pattern of the nano-titanium dioxide powder obtained in Comparative Example 1 of this invention;
[0025] Figure 4 This is the XRD pattern of the nano-titanium dioxide powder obtained in Comparative Example 2 of this invention;
[0026] Figure 5 This is a SEM image of the nano-titanium dioxide powder obtained in Example 1 of the present invention;
[0027] Figure 6 Here is a SEM image of the nano-titanium dioxide powder obtained in Example 2 of this invention;
[0028] Figure 7 This is a SEM image of the nano-titanium dioxide powder obtained in Example 3 of the present invention;
[0029] Figure 8 This is a SEM image of the nano-titanium dioxide powder obtained in Comparative Example 1 of this invention.
[0030] Figure 9 This is a SEM image of the nano-titanium dioxide powder obtained in Comparative Example 2 of this invention. Detailed Implementation
[0031] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0032] Example 1:
[0033] The preparation method of anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis includes the following steps:
[0034] (1) Prepare solution A by mixing water and isopropanol in a volume ratio of 1:5;
[0035] (2) Add citric acid to titanium tetrachloride solution and mix thoroughly to obtain solution B, wherein the concentration of titanium tetrachloride solution is 1.1 mol / L. -1 The amount of citric acid used is 0.5 wt.% of titanium tetrachloride;
[0036] (3) Then, under stirring, solution B is gradually added dropwise to solution A. The addition is completed in 30 minutes. Stirring is then stopped to obtain solution C.
[0037] (4) Add 25% ammonia water to solution C to adjust the pH to 8, then heat to 75℃ and keep warm for 3 hours;
[0038] (5) After step (4) is completed, the mixture is cooled to room temperature and aged for 24 hours to obtain nano-titanium dioxide slurry;
[0039] (6) The nano-titanium dioxide slurry is repeatedly washed with water and filtered to obtain a purified slurry;
[0040] (7) The purified slurry is heated to 450°C at a heating rate of 2°C / min and calcined for 2 hours; then heated to 600°C at a heating rate of 5°C / min and calcined for 1 hour; then heated to 750°C at a heating rate of 3°C / min and calcined for 3 hours to obtain anatase nano titanium dioxide powder.
[0041] Example 2:
[0042] The preparation method of anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis includes the following steps:
[0043] (1) Prepare solution A by mixing water and ethanol in a volume ratio of 1:3 and mixing them thoroughly.
[0044] (2) Polyvinylpyrrolidone was added to a titanium tetrachloride solution and mixed thoroughly to obtain solution B, wherein the concentration of the titanium tetrachloride solution was 1.1 mol / L. -1 The amount of polyvinylpyrrolidone used is 0.8 wt.% of titanium tetrachloride;
[0045] (3) Then, under stirring, solution B is gradually added dropwise to solution A. The addition is completed in 20 minutes. Stirring is then stopped to obtain solution C.
[0046] (4) Add 25% ammonia solution to solution C to adjust the pH to 8, then heat to 80℃ and keep warm for 3 hours;
[0047] (5) After step (4) is completed, the mixture is cooled to room temperature and aged for 24 hours to obtain nano-titanium dioxide slurry;
[0048] (6) The nano-titanium dioxide slurry is repeatedly washed with water and filtered to obtain a purified slurry;
[0049] (7) The purified slurry is heated to 400°C at a heating rate of 2°C / min and calcined for 2 hours; then heated to 650°C at a heating rate of 5°C / min and calcined for 1 hour; then heated to 750°C at a heating rate of 3°C / min and calcined for 3 hours to obtain anatase nano titanium dioxide powder.
[0050] Example 3:
[0051] The preparation method of anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis includes the following steps:
[0052] (1) Prepare solution A by mixing water and n-octanol in a volume ratio of 1:6;
[0053] (2) Add sodium dodecyl sulfate to a titanium tetrachloride solution and mix thoroughly to obtain solution B, wherein the concentration of the titanium tetrachloride solution is 1.1 mol / L. -1 The amount of sodium dodecyl sulfate used is 1.0 wt.% of titanium tetrachloride;
[0054] (3) Then, under stirring, solution B is gradually added dropwise to solution A. The addition is completed in 40 minutes. Stirring is then stopped to obtain solution C.
[0055] (4) Add 25% ammonia water to solution C to adjust the pH to 8, then heat to 90℃ and keep warm for 3 hours;
[0056] (5) After step (4) is completed, the mixture is cooled to room temperature and aged for 24 hours to obtain nano-titanium dioxide slurry;
[0057] (6) The nano-titanium dioxide slurry is repeatedly washed with water and filtered to obtain a purified slurry;
[0058] (7) The purified slurry is heated to 400°C at a heating rate of 2°C / min and calcined for 2 hours; then heated to 650°C at a heating rate of 5°C / min and calcined for 1 hour; then heated to 750°C at a heating rate of 3°C / min and calcined for 3 hours to obtain anatase nano titanium dioxide powder.
[0059] Comparative Example 1: (No surfactant added, otherwise the same as Example 1)
[0060] The preparation method of anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis includes the following steps:
[0061] (1) Prepare solution A by mixing water and isopropanol in a volume ratio of 1:5;
[0062] (2) When preparing a solution with a concentration of 1.1 mol / L -1 The titanium tetrachloride solution is solution B;
[0063] (3) Then, under stirring, solution B is gradually added dropwise to solution A. The addition is completed in 30 minutes. Stirring is then stopped to obtain solution C.
[0064] (4) Add 25% ammonia water to solution C to adjust the pH to 8, then heat to 75℃ and keep warm for 3 hours;
[0065] (5) After step (4) is completed, the mixture is cooled to room temperature and aged for 24 hours to obtain nano-titanium dioxide slurry;
[0066] (6) The nano-titanium dioxide slurry is repeatedly washed with water and filtered to obtain a purified slurry;
[0067] (7) The purified slurry is heated to 450°C at a heating rate of 2°C / min and calcined for 2 hours; then heated to 600°C at a heating rate of 5°C / min and calcined for 1 hour; then heated to 750°C at a heating rate of 3°C / min and calcined for 3 hours to obtain nano titanium dioxide powder.
[0068] Comparative Example 2: (Only low-temperature calcination, otherwise the same as Example 1)
[0069] The preparation method of anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis includes the following steps:
[0070] (1) Prepare solution A by mixing water and isopropanol in a volume ratio of 1:5;
[0071] (2) Add citric acid to titanium tetrachloride solution and mix thoroughly to obtain solution B, wherein the concentration of titanium tetrachloride solution is 1.1 mol / L. -1 The amount of citric acid used is 0.5 wt.% of titanium tetrachloride;
[0072] (3) Then, under stirring, solution B is gradually added dropwise to solution A. The addition is completed in 30 minutes. Stirring is then stopped to obtain solution C.
[0073] (4) Add 25% ammonia water to solution C to adjust the pH to 8, then heat to 75℃ and keep warm for 3 hours;
[0074] (5) After step (4) is completed, the mixture is cooled to room temperature and aged for 24 hours to obtain nano-titanium dioxide slurry;
[0075] (6) The nano-titanium dioxide slurry is repeatedly washed with water and filtered to obtain a purified slurry;
[0076] (7) The purified slurry was heated to 550°C at a heating rate of 2°C / min and calcined for 2 hours to obtain nano titanium dioxide powder.
[0077] Comparative Example 3: (Only one roasting, otherwise the same as Example 1)
[0078] The preparation method of anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis includes the following steps:
[0079] (1) Prepare solution A by mixing water and isopropanol in a volume ratio of 1:5;
[0080] (2) Add citric acid to titanium tetrachloride solution and mix thoroughly to obtain solution B, wherein the concentration of titanium tetrachloride solution is 1.1 mol / L. -1 The amount of citric acid used is 0.5 wt.% of titanium tetrachloride;
[0081] (3) Then, under stirring, solution B is gradually added dropwise to solution A. The addition is completed in 30 minutes. Stirring is then stopped to obtain solution C.
[0082] (4) Add 25% ammonia water to solution C to adjust the pH to 8, then heat to 75℃ and keep warm for 3 hours;
[0083] (5) After step (4) is completed, the mixture is cooled to room temperature and aged for 24 hours to obtain nano-titanium dioxide slurry;
[0084] (6) The nano-titanium dioxide slurry is repeatedly washed with water and filtered to obtain a purified slurry;
[0085] (7) The purified slurry is heated to 600°C at a heating rate of 5°C / min and calcined for 6 hours to obtain nano titanium dioxide powder.
[0086] Comparative Example 4: (Only two calcinations were performed; all other aspects were the same as in Example 1)
[0087] The preparation method of anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis includes the following steps:
[0088] (1) Prepare solution A by mixing water and isopropanol in a volume ratio of 1:5;
[0089] (2) Add citric acid to titanium tetrachloride solution and mix thoroughly to obtain solution B, wherein the concentration of titanium tetrachloride solution is 1.1 mol / L. -1 The amount of citric acid used is 0.5 wt.% of titanium tetrachloride;
[0090] (3) Then, under stirring, solution B is gradually added dropwise to solution A. The addition is completed in 30 minutes. Stirring is then stopped to obtain solution C.
[0091] (4) Add 25% ammonia water to solution C to adjust the pH to 8, then heat to 75℃ and keep warm for 3 hours;
[0092] (5) After step (4) is completed, the mixture is cooled to room temperature and aged for 24 hours to obtain nano-titanium dioxide slurry;
[0093] (6) The nano-titanium dioxide slurry is repeatedly washed with water and filtered to obtain a purified slurry;
[0094] (7) The purified slurry is heated to 750°C at a heating rate of 3°C / min and calcined for 6 hours to obtain nano titanium dioxide powder.
[0095] Comparative Example 5: (The surface dispersant was added last; everything else was the same as in Example 1)
[0096] The preparation method of anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis includes the following steps:
[0097] (1) Prepare solution A by mixing water and isopropanol in a volume ratio of 1:5;
[0098] (2) Under stirring conditions, the concentration was 1.1 mol L -1 Titanium tetrachloride solution was gradually added dropwise to solution A, and the addition was completed in 30 minutes. Stirring was then stopped to obtain solution B.
[0099] (3) Add citric acid to solution B and mix well to obtain solution C, wherein the amount of citric acid used is 0.5 wt.% of titanium tetrachloride;
[0100] (4) Add 25% ammonia water to solution C to adjust the pH to 8, then heat to 75℃ and keep warm for 3 hours;
[0101] (5) After step (4) is completed, the mixture is cooled to room temperature and aged for 24 hours to obtain nano-titanium dioxide slurry;
[0102] (6) The nano-titanium dioxide slurry is repeatedly washed with water and filtered to obtain a purified slurry;
[0103] (7) The purified slurry is heated to 450°C at a heating rate of 2°C / min and calcined for 2 hours; then heated to 600°C at a heating rate of 5°C / min and calcined for 1 hour; then heated to 750°C at a heating rate of 3°C / min and calcined for 3 hours to obtain nano titanium dioxide powder.
[0104] The nano-titanium dioxide powders obtained in the examples and comparative examples were subjected to XRD and SEM detection. Based on the SEM images, at least 200 particles were selected using a Nano Measurer to obtain the average particle size. The specific surface area was obtained based on nitrogen adsorption-desorption tests. The results are shown in Table 1.
[0105] Table 1
[0106]
[0107] It can be seen that the anatase nano-titanium dioxide yield of Examples 1-3 reached over 91.2%, with a particle size of 30.36-36.27 nm. At the same time, the anatase crystal form accounted for over 96% of the prepared nano-titanium dioxide, and could even reach 100%. However, although Comparative Example 3 had a higher titanium dioxide yield, its anatase titanium dioxide content was lower. Although Comparative Example 5 produced titanium dioxide that was entirely anatase, its titanium dioxide yield was lower.
Claims
1. A method for preparing anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis, characterized in that, Includes the following steps: (1) Mix water and alcohol to obtain solution A; (2) Add a surface dispersant to the titanium tetrachloride solution and mix thoroughly to obtain solution B; (3) Then, under stirring, add solution B dropwise into solution A. After the addition is complete, stop stirring to obtain solution C. (4) Add alkali to solution C to adjust the pH to 7-10, then raise the temperature to 70-90℃ and keep it warm for 3-10 hours; (5) After step (4) is completed, age for 12 to 36 hours to obtain nano titanium dioxide slurry; (6) The nano-titanium dioxide slurry is washed with water and filtered to obtain a purified slurry; (7) The purified slurry is calcined to obtain anatase nano-titanium dioxide; the calcination includes low-temperature calcination, primary calcination and secondary calcination, the low-temperature calcination temperature is 400-550℃ and the time is 1-2h, the primary calcination temperature is 600-700℃ and the time is 1-2h, and the secondary calcination temperature is 750-800℃ and the time is 2-4h.
2. The method for preparing anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis according to claim 1, characterized in that: The alcohol in step (1) is selected from one of n-propanol, n-octanol, isopropanol, ethanol, and butanol.
3. The method for preparing anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis according to claim 1 or 2, characterized in that: In step (1), the volume ratio of water to alcohol is 1:1 to 10.
4. The method for preparing anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis according to claim 1, characterized in that: In step (2), the surface dispersant is selected from citric acid, polyethylene glycol, sodium dodecyl sulfate, and polyvinylpyrrolidone.
5. The method for preparing anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis according to claim 1 or 4, characterized in that: The concentration of the titanium tetrachloride solution in step (2) is 1.0–1.2 mol·L⁻¹. -1 The amount of surface dispersant added is 0.1 to 1 wt.% of titanium tetrachloride.
6. The method for preparing anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis according to claim 1, characterized in that: In step (3), the time for solution B to be added to solution A is 20 to 40 minutes.
7. The method for preparing anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis according to claim 1, characterized in that: In step (7), the purified slurry is heated to 400-550°C at a rate of 1-3°C / min, and then calcined at low temperature for 1-2 hours.
8. The method for preparing anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis according to claim 1, characterized in that: The first roasting in step (7) involves heating the material after low-temperature roasting to 600-700℃ at a rate of 4-6℃ / min, and then roasting for 1-2 hours.
9. The method for preparing anatase nano-titanium dioxide based on low-temperature alcohol hydrolysis according to claim 1, characterized in that: The secondary roasting in step (7) involves heating the material after the first roasting to 750-800℃ at a rate of 2-4℃ / min, and then roasting for 2-4 hours.
Citation Information
Patent Citations
Preparation method of spheroidized nano titanium dioxide
CN115259214A
Preparation method of battery-grade nano titanium dioxide
CN117865215A
Method for preparing anatase type nano-titanium dioxide
CN101318698A
